2008
DOI: 10.1016/j.jocd.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Mass Is More Strongly Related to Hip Bone Mineral Density Than Is Quadriceps Strength or Lower Activity Level in Adults Over Age 50Year

Abstract: This cross-sectional study examined whether reduced hip bone mineral density (BMD) is better explained by isokinetic knee extensor strength (KES), lower limb lean body mass (L-LBM), or activity level (PASE). Through population-based recruitment, 1543 adults without knee osteoarthritis were recruited. For men and women respectively, means ± SD were: Age 60.8±8.0 and 61.1±7.9 years; BMI 29.6±4.6 and 29.1±5.4 kg/m2; hip BMD 1.025±0.138 and 0.895±0.128 g/cm 2 ; KES 124.9 ±41 and 72.7±22.9 N•m; L-LBM 10.3±1.5 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 32 publications
7
58
2
1
Order By: Relevance
“…Among physical performance, chair stand up time had correlated significantly with bone mineral density at all the measured sites, but the correlation was not as strong as for CC at hip. The finding is similar to prior studies showing that muscle mass is a better predictor of BMD compared to physical ability [34].…”
Section: Discussionsupporting
confidence: 90%
“…Among physical performance, chair stand up time had correlated significantly with bone mineral density at all the measured sites, but the correlation was not as strong as for CC at hip. The finding is similar to prior studies showing that muscle mass is a better predictor of BMD compared to physical ability [34].…”
Section: Discussionsupporting
confidence: 90%
“…This finding was expected, as numerous other researchers have reported similar findings (3, 20, 29, 34, 35). Strong evidence supports the contribution of these factors to BMD.…”
Section: Discussionsupporting
confidence: 88%
“…However, the beneficial effects of exercise on BMD may be mitigated by the fact that the greater body mass of heavier individuals has a protective effect against bone loss because of the concomitant increases in longitudinal loading of the skeleton from the larger body mass as well as the greater muscle forces required to move a larger person (2, 3, 14, 29). Previous data confirm that elite highly-competitive elderly athletes have less body mass than do healthy age-matched controls (18).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly the case among elderly men [23], because men have more muscle mass than women [24]. In line with this, studies have shown that lean mass was an independent contributor to hip bone mineral density [25, 26], especially in men [26, 27]. Furthermore, decreased lean mass may reduce testosterone level [28, 29], which has been shown to be positively associated with muscle strength and bone mineral density [28].…”
Section: Discussionmentioning
confidence: 95%